Answers

2014-07-01T11:17:54+08:00
Use special products for this:

Cube of a trinomial:
               (a-b)³ = a³ - 3a²b + 3ab² - b³

Just substitute and simplify, and let:
 
                        a = 3x
                        b = 6y

So we will have:
                       
                   (a-b)³ = a³ - 3a²b + 3ab² - b³
                    (3x - 6y)³ = (3x)³ - 3(3x)²(6y) + 3(3x)(6y)² - (6y)³
                                  = 27x³ - 3(9x²)(6y) + 3(3x)(36y²) - 216y³
                                  = 27x³ - 162x²y + 324xy² - 216y³ ......ANSWER


2 3 2